IDENTIFYING ACTORS AND THEIR INTEREST IN THE COMMUNITY BASED FOREST MANAGEMENT (CBFM) AREA OF PUNTANA, SOUTHERN LEYTE (PHILIPPINES) - Small, Karen; Rodrigo, Ruffy Miliang (Journal of Agriculture and Technology Management; Vol 21 No 1 (2018): Journal of Agriculture and Technology Management (JATM) Volume 21 January - June 2018 Issue, 2018)
The Philippines adopted the Community Based Forest Management (CBFM) program as a national strategy to ensure sustainable forest management in the country's forestlands. This research was conducted to explore the main actors and their interests, and the potential synergy in the implementation of the program in Puntana, Southern Leyte, Philippines. Primary and secondary data were collected through semi-structured questionnaires, in-depth interviews with the preidentified actors and observation in the field based on the actors’ response. The study recorded diverse interests among the nine actors. In addition, the model displayed diverse interests that actors have in conflict. Nevertheless, potential synergies revealed that despite different interests, the main actors could still work together in line with the principles of sustainable forest management. This information is useful for carrying out future activities primarily in the decision-making process of attaining the overall objective of the CBMF program in the country.